Association Between Menstrual Disorders and Obesity-Related Anthropometric Indices in Female High School Students: A Cross-Sectional Study - Mostafa Rad; Marzieh Torkmannejad Sabzevary; Zahra Mohebbi Dehnavi (Shiraz University of Medical Sciences, 2018)
Background: The menstrual cycle determines the health of women. Menstrual disorders are a major Geneologic problem among women, especially adolescents, which is a major source of anxiety for them and their families. Factors such as BMI, exercise, and stress can be related to menstrual disorders. As a result, this study was conducted to determine the association between menstrual disorders and anthropometric indices in Female High School Students. Methods: This descriptive cross-sectional study was conducted in Sabzevar on 200 high school female students in 2017. The participants first completed the personal, midwifery, and family profile questionnaire. Finally, anthropometric indicators were measured. Data analysis was done using SPSS 16 software and Mann-Whitney test. Results: The results of the study showed that oligomenorrhea with weight (p = 0.03), arm circumference (P = 0.03), BMI (P = 0.03), hypermenorrhea with waist circumference (P = 0.01), hypomenorrhea with height (P = 0.04), menorrhagia with waist circumference (P = 0.002), polymenorrhea with weight (P = 0.01), arm circumference (P = 0.04), Body mass index (p = 0.01) and metrorrhagia with weight (P = 0.01), hip circumference (P = 0.007), waist circumference (P = 0.004), and hip circumference (P = 0.01) have a significant association. Conclusions: The results of this study showed that some anthropometric indices associated with menstrual disorders in female high school students. According to the results of this study, it seems that having a suitable lifestyle can prevent these disorders.